Implementation of the Garbage Management Plan by MARPOL Annex V on the SV. Patrona 118: Penerapan Garbage Management Plan sesuai Marpol Annex V di SV. Patrona 118 - Sabaruddin; Nurmala, Eka; Baihaqi, Baihaqi; R., Sulastriani; Mahyuzar, Ardiansyah (ALTAIR: Jurnal Transportasi dan Bahari, 2024)
Marine pollution is a condition that endangers the lives of marine life, natural resources, the health of marine ecosystems, and human health. To reduce marine pollution produced by ships, all crew members (ABK) are responsible and have the necessary knowledge and skills. Garbage Management Plan is a plan for handling waste. This includes understanding the types of waste and how to manage it effectively so that it can be separated and disposed of according to its kind. The author conducted research on a ship based on qualitative research, where the author has carried out sea practice for more than a year on the SV. Patrona 118. In this sea practice the author observed the use of the Garbage Management Plan on the Patrona 118 Supply Vessel according to MARPOL Annex V. The results of this study are: 1) To protect the marine environment effectively, the ship's crew must increase awareness and discipline in following these regulations. Companies need to ensure that all types of waste, especially plastic, are managed and disposed of properly by applicable provisions; and 2) Although the majority of the crew have understood and complied with the existing procedures, increased supervision, and training are essential steps to achieve knowledge of the entire crew and full compliance and prevention of marine pollution by MARPOL 73/78 Annex V.